Fiber Strain Measurement for Wide Region Quasidistributed Sensing by Optical Correlation Sensor with Region Separation Techniques. (20th June 2010) - Xu, Xunjian; Bueno, Antonio; Nonaka, Koji; Sales, Salvador
Abstract : The useful application of optical pulse correlation sensor for wide region quasidistributed fiber strain measurement is investigated. Using region separation techniques of wavelength multiplexing with FBGs and time multiplexing with intensity partial reflectors, the sensor measures the correlations between reference pulses and monitoring pulses from several cascadable selected sensing regions. This novel sensing system can select the regions and obtain the distributed strain information in any desired sensing region.